2019
DOI: 10.1016/j.cell.2019.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Continual Learning in a Multi-Layer Network of an Electric Fish

Abstract: Highlights d Biological solutions to general problems in multi-layer learning are shown d Intermediate layer function requires compartmentalization of learning and signaling d Circuit organization based on learning solves the credit assignment problem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 55 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…In the cerebellum-like circuit of the electric fish, MG-cells, which are analogous to P-cells, produce broad spikes that are analogous to complex spikes. An unexpected sensory input produces broad spikes in some MGcells, but suppresses the broad spikes in others (Muller et al, 2019). Thus, MG-cells in the electric fish also exhibit a tuning for error.…”
Section: Population Coding Of P-cellsmentioning
confidence: 99%
“…In the cerebellum-like circuit of the electric fish, MG-cells, which are analogous to P-cells, produce broad spikes that are analogous to complex spikes. An unexpected sensory input produces broad spikes in some MGcells, but suppresses the broad spikes in others (Muller et al, 2019). Thus, MG-cells in the electric fish also exhibit a tuning for error.…”
Section: Population Coding Of P-cellsmentioning
confidence: 99%
“…In these electrolocation systems, corollary discharge functions to subtract predictive sensory feedback from reafferent input by a modifiable efference copy, forming a "negative image" through cerebellum-like circuitry in the electrosensory lateral line lobe (24,55,56). This negative image is formed at synapses between parallel fibers that carry corollary discharge inputs from the CN and medial ganglion cells that receive sensory inputs through spike-timing-dependent plasticity (59)(60)(61)(62). By contrast, in the communication pathway, we found that removal of sensory feedback had no effect on hormonal modulations of corollary discharge (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The targets were smoothed broad-spike responses of 15 MG cells time-locked to an electric organ discharge command measured during experiments ( Muller et al, 2019 ). The original data set consisted of 55 MG cells, each with a 300ms long spike raster with a 1ms time bin.…”
Section: Methodsmentioning
confidence: 99%